Demokratyczny status sądowej kontroli konstytucyjności prawa - Ciszewski, Wojciech (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
Constitutional review of legislation is the power to examine statutes for their conformity with the constitution. This competence is performed by the judiciary. The origins of this institution date back to XIX century and since that time constitutional review of legislation has became an important institution in most democratic states. In the paper, the author answers the most important charge raised against constitutional review – that it lacks democratic legitimacy. According to Jeremy Waldron, there is always a loss to democracy when a majoritian decision is overruled by a politically unaccountable court. As an answer to Waldron’s objection, the author introduces three arguments for the democratic status of constitutional review. These arguments point to three different sources of legitimacy for constitutional review: democratic will of the people, the principle of respect for the democratic reason, and substantial democratic values.